Wearable Plasma Pads for Biomedical Applications - Junggil Kim; Kyong-Hoon Choi; Yunjung Kim; Bong Joo Park; Guangsup Cho (Applied Sciences, 2017)
A plasma pad that can be attached to human skin was developed for aesthetic and dermatological treatment. A polyimide film was used for the dielectric layer of the flexible pad, and high-voltage and ground electrodes were placed on the film surface. Medical gauze covered the ground electrodes and was placed facing the skin to act as a spacer; thus, the plasma floated between the gauze and ground electrodes. In vitro and in vivo biocompatibility tests of the pad showed no cytotoxicity to normal cells and no irritation of mouse skin. Antibacterial activity was shown against Staphylococcus aureus and clinical isolates of methicillin-resistant S. aureus. Furthermore, skin wound healing with increased hair growth resulting from increased exogenous nitric oxide and capillary tube formation induced by the plasma pad was also confirmed in vivo. The present study suggests that this flexible and wearable plasma pad can be used for biomedical applications such as treatment of wounds and bacterial infections.